THE EFFECT OF EARLY MOBILIZATION TOWARDS SELF-CARE LEVELS IN POSTSECTIO CAESAREA MOTHER WITH SELFCARE THEORY APPROACH - Wahyuni, Fitri; Pradanie, Retnayu; Aulia Nastiti, Aria; Ketut Alit Armini, Ni (International Journal of Psychosocial Rehabilitation, 2020)
Background: The number of Sectio Caesarea (SC, or C-Section) births in Indonesia is quite high compared to other countries in Asia. Participation and independence of the mother in postpartum care are needed so that the healing process of the post-SC body can be optimal. Early mobilization is considered an effort to help speed up the healing of organ systems and their function in the body. However, there are still many post-SC mothers who do not do early mobilization. Purpose: This research aims to find out whether there is an influence of early mobilization on the degree of independence of care in post-SC mothers. Method: This research is a quasi-experimental post-test only with a control group design. Research instruments include checklists and observation sheets arranged by Nursing Outcomes Classification (NOC). The population of this study was 36 people, and the sample size that met the inclusion criteria was 30 people for the treatment and control groups, respectively. Data was analyzed using the Mann-Whitney Test. Results: The majority of the respondents’ age range of 20-25 years and the most labor status are having been through SC for 2 times or more. In the previous type of childbirth, the majority of the treatment group had spontaneous vaginal delivery (70.6%), while in the control group the most previous labor was SC (61.1%). At the level of independence, the control group was in the category of needing assistance (43%), while the treatment group was in the independent category (86.7%). The results of the data test stated that there were differences between the results of the posttest in the control and treatment groups with p = 0.004. Conclusion: There is an influence of early mobilization on the level of self-care independence in post-SC mothers.